Hack your hardware. - Stern, Zack.
Want get more out of your desktop PC, cell phone, Wi-Fi network, and other devices? our hands-on guide shows you how to make your tech gear faster, more powerful, and more versatile than ever.
Keywords: Computer security; IEEE 802.11 (Standard); Video games; iPhone (Smartphone); Cell phones; Digital cameras; Hacking; Wireless routers; Nvidia control; Wi-Fi.; Universal remote